MANHAJ AL-HAKIM AL-NAISABURI DALAM AL-MUSTADRAK ‘ALA SHAHIHAIN - Rizqa Amelia (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
One of the interesting Hadith scholars in the 4th century H was Imam al-Hakim anNaisaburi with his monumental work al-Mustadrak 'alȃ as-Sahīhain. Imam alHakim as mukharrij is interesting to discuss because of the many discussions and debates surrounding his personality, his works, and the methods used in compiling his Hadith books. Many discussions related to his personality debated whether he was a Sunni or Shiite theologian. As for the method or manhaj, is it true that he applied double standards in assessing Hadith, as well as the status of hadith in his al-Mustadrak as he stated using the conditions of al-Bukhari and Muslim which according to other scholars he did not fully use correctly, even considered there are still many shortcomings. Therefore, the author feels it is very important to discuss this matter explicitly and in detail so that there will be no confusion of understanding for us, besides that it will also add to our insights as academics in Hadith studies.